P0424CLINICO-PATHOLOGICAL CHARACTERISTICS AND OUTCOMES OF PATIENTS WITH DNAJB9 POSITIVE FIBRILLARY GLOMERULONEPHRITIS. (6th June 2020) - Liang, Shaoshan; Liang, Dandan; Xu, Feng; Zhang, Mingchao; Yang, Fan; Li, Ping; Zeng, Caihong
Abstract: Background and Aims: To investigate the clinicopathological features and prognosis of DNAJB9 positive fibrillary glomerulonephritis (FGN) in a single center in China. Method: Cases diagnosed as FGN by renal biopsy from January 2011 to December 2019 in Jinling Hospital were stained with anti-DNAJB9 by immunohistochemistry. The patients with DNAJB9 positive FGN were retrospective analyzed. Results: DNAJB9 staining of glomerular deposits was seen in 6 cases of FGN. 1 man and 5 women with a median age of 26 years (range, 21 to 49 years) were studied. Underlying autoimmune disease of Sjogren's syndrome and Hashimoto thyroiditis was in 1 case. None of them had dysproteinemia, malignancy, hepatitis C, hepatitis B, cryoglobulinemia, or diabetes. The patients presented with hypertension and edema in 5 cases, renal insufficiency in 1 case, and proteinuria in 6 cases with the median 24-hour urine protein 2.58 g (range, 1.66 to 9.57 g), nephrotic syndrome in 3 cases, and microscopic hematuria in 2 cases. The histologic pattern was mesangial proliferative glomerulonephritis (GN) and membranoproliferative GN. A mean of 9.7% of glomeruli were globally sclerotic. Crescents were present in 1 case (10%). The degree of tubular atrophy and interstitial fibrosis were absent (2 cases) and mild (4 cases), and severe acute tubular injury was in 1 case. All 6 cases showed glomerular positivity for IgG, C3 and C1q, 5 of which were positive for IgM, and 4 of which were positive for IgA. The glomerular deposits stained for polyclonal IgG subclasses and both kappa and lambda light chains in 3 cases. In 1 case, it stained for polyclonal IgG subclasses without kappa or lambda. IgG subclasses were IgG4 dominant in 3 cases and IgG1 dominant in 1 case. In 2 cases, they stained for monoclonal IgG1-kappa and IgG1-lambda. On electron microscopy (EM), the fibrillary deposits were seen infiltrating the mesangium, subendothelial, subepithelial area in all 6 cases, and the lamina densa of the GBMs in 5 cases with diameter of 7-40nm. Combined with observation of DNAJB9 staining, immunofluorescence microscopy and EM, extraglomerular deposits were identified in vessel walls in 5 cases, tubular basement membranes in 3 cases, peritubular capillaries in 3 cases. Congo red positivity was in 4 cases. At a median time of 32.9 months (range, 1 to 68.3 months) after biopsy, 3 cases were stable, 1 case had partial renal function recovery, and 2 cases had partial remission of proteinuria. Conclusion: DNAJB9 immunohistochemistry is sensitive and specific for FGN. Monoclonal IgG and light chain was observed in young patients. Extraglomerular deposits were common. Prognosis was good in this young patient's series.